Image encryption algorithm based on dynamic DNA coding operations and 3D chaotic systems - Kengnou Telem, Adélaïde Nicole; Fotsin, Hilaire Bertrand; Kengne, Jacques (Multimedia tools and applications, 2021)
This paper presents a new image encryption algorithm based on 3D chaotic system and deoxyribonucleic acid (DNA) coding. It uses two keys, an external one of 128 bits long and an internal one of 64 gray values coming from the plain image. The initial conditions come from the two keys and vary from one line of the image to the other and from one image to the other and consequently the sequences of substitutions too. In general, in image encryption based on 3D chaotic systems, each chaotic variable is used independently of the others in one phase of the encryption. Here we use the zigzag process to combine the sequences from all the variables before using them simultaneously in the encryption process. DNA coding generally uses one of the 24 DNA rules and one of the 16 join operations to perform the encryption. Here we use all the 24 rules dynamically as well as the 16 join operations in the encryption. Also we apply the chaotic permutation on DNA chain. The logical DNA operations are used according to an algorithm similar to that of the Fast Walsh Transform (FWT) in those 24 DNA rules. The algorithm has been evaluated. It has good statistical properties of cipher images. The proposed system presents high sensitivity on the encryption-decryption keys and on the plain images. These latter features make the proposed algorithm very efficient, robust and resistant against brute force attacks and good for the future secure image communication.